The role of primary health care nurses in the care of women victims of violence - Borges Bueira da Silva, Marina; Samantha Martins de Souza, Janaina; Matte, Juliana (Disciplinarum Scientia | Saúde, 2024)
Violence Against Women (VAW) is recognized as a significant violation upon human rights, specifically encroaching upon women’s entitlements to life, health, and physical well-being. It has the potential to impact women across different social classes, age groups, beliefs, marital statuses, and sexual orientations, regardless of geographical location. This study aims to determine the specific responsibilities and contributions of primary health care nurses in providing care for women who have experienced violence. To accomplish this goal, we conducted a preliminary investigation using a quantitative methodology in April 2022. This investigation involved administering a questionnaire consisting of 12 questions to a sample of 25 primary health care nurses in the municipality of Bento Gonçalves/RS - in the south of Brazil. We used descriptive statistics to analyze the data. The primary findings indicate a deficiency in the understanding of existing legislation pertaining to violence against women among nurses, as well as a lack of adequate training provided by higher education institutions for future professionals. It is crucial to provide comprehensive training to healthcare professionals on legislation, enabling them to effectively inform victims about their rights and relevant support services.